OBJECT ORIENTED PROGRAMMING IN TEACHING - KUBRICKY, Jan; KLEMENT, Milan (Journal of Technology and Information Education, 2009)
The paper deals with Object Oriented Programming. It reviews the opinions of eminent educators - programmers and focuses on object-oriented possibilities in the design and direction of web apllications.
Keywords: object oriented programming; teaching of programming; web apllication; programming language.